Degradation of the insecticide alfacipermethrin by Trichoderma harzianum - Mayra Karina Gutiérrez-Araujo (2017)
It was determined whether Trichoderma harzianum was capable of degrading the insecticide alphacipermethrin. T. harzianum was seeded in Papa Dextrose Agar and incubated for 7 days, then petri dishes were prepared with minimal gar of salts containing concentrations of 0, 75, 100 and 150 ppm of alphacipermethrin respectively, in which were seeded mycelium of the fungus was incubated at 25 °C for 3 days, radial growth being evaluated daily. The degradation of alphacipermethrin in broth was also evaluated for which 8 mL of a suspension of 106 spores / mL of T. harzianum were inoculated into flasks containing minimal broth of salts with 0, 75, 100 and 150 ppm of alpha- 10 days. The broth was then filtered and the obtained mycelium was oven dried and weighed. The broth remaining after the filtrate was analyzed by thin layer chromatography to detect whether there was or was no presence of alphacipermethrin, analyzing the data obtained by ANAVA. In solid medium it was found that T. harzianum at the 75 ppm concentration of alphacipermethrin grew 30.54% with respect to the control, whereas in the concentration 100 ppm and 150 ppm presented a growth of 41.62 and 52.40% respectively. Regarding dry weight, it was observed that in the concentrations of 75, 100 ppm and 150 ppm weight, 37.26, 44.34 and 52% in comparison to the control respectively; whereas in the chromatography there was no presence of the alphacipermethrin in any of the evaluated concentrations. It is concluded that T. harzianum is capable of degrading the alphacipermethrin at concentrations of 75, 100, 150 ppm.